Language Documentation As A Revitalization Effort Regional Languages Are Starting To Extinct - Ade Rahima (International Journal of Multidisciplinary Sciences and Arts, 2024)
The main aim of this research study is to determine the level of condition or vitality status of a language. This can be directed at saving this language from extinction. The method used in this research is Action Research. The status of the language from the results of the study has implications for the actions that need to be taken for the language in question, whether conservation, revitalization, or both conservation and revitalization need to be carried out. For example, conservation actions in the form of documentation alone can be carried out if the language is categorized as extinct or needs to be carried out at the same time as conservation and revitalization if the language is categorized as almost extinct or threatened with extinction.The conclusion of this research is that documenting languages ??is actually the first step in efforts to revitalize endangered languages. The success of revitalization still depends on the speaking community itself.